PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA PERUSAHAAN : UKURAN PERUSAHAAN , KETIDAKPASTIAN LINGKUNGAN DAN STRATEGI (SEBAGAI VARIABEL ANTESEDEN) KAPABILITAS PERUSAHAAN (SEBAGAI VARIABEL INTERVENING) - Nurainun Nurainun; Ria Nelly Sari; Pipin Kurnia (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
This research aims to determine the competence of influence of managementcontrol system to firm performance: company size, environmental uncertainty andstrategy (as antecedent variable) company capability (as intervening variable). Thisresearch used sampling census method. The population in this study are allmanufacturing companies listed in Indonesia Stock Exchange (IDX).Sampel in thisresearch is the whole of the population, and respondents: Chief Financial Officer(CFO), representatives them and Head of the Department of Finance / Accountingand Internal Auditor at 143 manufacturing companies listed in Indonesia StockExchange (IDX). Data collection techniques used is by distributing questionnairessent in the form of Softfile / google form (by email) to each company. Data analysistechnique using SEM model (Structural Equation Modeling) with the help ofWarpPLS 6.0 program. . In addition, to test the seventh hypothesis, the VAF methodis used to test the intervening variables in the hypothesis. The results of testing thehypothesis in this study indicate that (1) the company size does not influence themanagement control system, (2) uncertainty of the environment influence themanagement control system, (3) strategies influence the management controlsystem, (4) SPM in the form of beliefs systems, boundary system, diagnosticscontrol system, and control systems interactive effect to capability company, (5)capability company in the form of market orientation, innovation, organizationallearning, and entrepreneurship has a positive effect to firm performance, (6) MCSconsists of the beliefs system, boundary system, diagnostic control system, andinteractive control system have an effect to firm performance (7) MCS influence tofirm performance with company capability as intervening variable.